Characterization of MDR and XDR Streptococcus pneumoniae in Canada, 2007–13. (28th April 2015) - Golden, Alyssa R.; Rosenthal, Margot; Fultz, Ben; Nichol, Kimberly A.; Adam, Heather J.; Gilmour, Matthew W.; Baxter, Melanie R.; Hoban, Daryl J.; Karlowsky, James A.; Zhanel, George G.
Abstract: Objectives: The goal of this study was to characterize Streptococcus pneumoniae demonstrating MDR (resistant to three or more antimicrobial classes) or XDR (resistant to five or more classes) phenotypes, collected from Canada during the CANWARD 2007–13 study. Methods: From 2007 to 2013 inclusive, S. pneumoniae isolates were collected as a part of the CANWARD surveillance study. MDR and XDR isolates were subjected to PFGE, MLST, molecular detection of pneumococcal pili and macrolide resistance determinants mef (A/E) and erm (B), sequencing of PBPs 1A, 2B and 2X and comparison with Pneumococcal Molecular Epidemiology Network (PMEN) clones. Results: Of 2129 S. pneumoniae isolates collected during the CANWARD 2007–13 study, 61 (2.9%) were found to be MDR. Of these MDR isolates, 43 (70.5%) were XDR. The most common serotypes for both MDR and XDR S. pneumoniae were 19A and 19F. Twenty-nine of 61 isolates (48%) demonstrated resistance to clarithromycin, clindamycin, doxycycline, penicillin and trimethoprim/sulfamethoxazole. All isolates possessed at least one macrolide resistance determinant and mutations in PBPs 1A, 2B and 2X. The most common clone was piliated, XDR ST320, an internationally circulating double-locus variant of Taiwan 19F -14 (ST236). Conclusions: Though the rate of MDR S. pneumoniae has remained relatively stable since 2007, XDR strains have emerged in Canada. These strains are virulent, possess resistance determinants and are related to international clones.